Association Between Regular Laxative Use and Incident Dementia in UK Biobank Participants. (18th April 2023) - Yang, Zhirong; Wei, Chang; Li, Xiaojuan; Yuan, Jinqiu; Gao, Xuefeng; Li, Bingyu; Zhao, Ziyi; Toh, Sengwee; Yu, Xin; Brayne, Carol; Yang, Zuyao; Sha, Feng; et al.
Abstract : Background and Objectives: The use of over-the-counter laxatives is common in the general population. The microbiome-gut-brain axis hypothesis suggests that the use of laxatives could be associated with dementia. We aimed to examine the association between the regular use of laxatives and the incidence of dementia in UK Biobank participants. Methods: This prospective cohort study was based on UK Biobank participants aged 40–69 years without a history of dementia. Regular use of laxatives was defined as self-reported use in most days of the week for the last 4 weeks at baseline (2006–2010). The outcomes were all-cause dementia, Alzheimer disease (AD), and vascular dementia (VD), identified from linked hospital admissions or death registers (up to 2019). Sociodemographic characteristics, lifestyle factors, medical conditions, family history, and regular medication use were adjusted for in the multivariable Cox regression analyses. Results: Among the 502, 229 participants with a mean age of 56.5 (SD 8.1) years at baseline, 273, 251 (54.4%) were female, and 18, 235 (3.6%) reported regular use of laxatives. Over a mean follow-up of 9.8 years, 218 (1.3%) participants with regular use of laxatives and 1, 969 (0.4%) with no regular use developed all-cause dementia. Multivariable analyses showed that regular use of laxatives was associated with increased risk of all-cause dementia (hazard ratio [HR] 1.51; 95% CI 1.30–1.75) and VD (HR 1.65; 95% CI 1.21–2.27), with no significant association observed for AD (HR 1.05; 95% CI 0.79–1.40). The risk of both all-cause dementia and VD increased with the number of regularly used laxative types ( p trend 0.001 and 0.04, respectively). Among the participants who clearly reported that they were using just 1 type of laxative (n = 5, 800), only those using osmotic laxatives showed a statistically significantly higher risk of all-cause dementia (HR 1.64; 95% CI 1.20–2.24) and VD (HR 1.97; 95% CI 1.04–3.75). These results remained robust in various subgroup and sensitivity analyses. Discussion: Regular use of laxatives was associated with a higher risk of all-cause dementia, particularly in those who used multiple laxative types or osmotic laxative.